THE TRANSITION TO ELECTRIC VEHICLES FOR THE SUSTAINABLE FUTURE OF THE JAKARTA METROPOLITAN AREA - Muhammad Alfarizi; Rini Kurnia Sari; Rafialdo Arifian (Jurnal Kebijakan Pembangunan Daerah, 2024)
Global population growth and improved transportation The Jakarta metropolitan area contributes significantly to greenhouse gas emissions. The DKI Jakarta Provincial Government has implemented policies to encourage the adoption of electric vehicles, but the growth of electric vehicles in the Jakarta Metropolitan Area still faces challenges. The study aims to investigate the psychological and social factors influencing people's intention to switch to electric vehicles and their contribution to the region's Sustainable Development Goals (SDGs). The quantitative approach was taken using an online survey method on 200 Jakarta metropolitan communities with a purposive sampling withdrawal technique. This study chose the Partial Least Square-Structural Equation Modeling (PLS-SEM) analysis technique. The analysis showed that electric vehicle knowledge and environmental concern significantly positively affected subjective norms, attitudes and perceived behavioural control. These three psychological drivers found their role in the intention to switch to electric vehicles and SDGs Contribution. Recommendations focused on strengthening fiscal transportation policies, supporting infrastructure and sustainable transportation planning at metropolitan Jakarta and national scales.